Investigating the environmental Kuznets curves through the economic globalization lens: evidence from middle income countries - Narandaran, Yasmin Yashodha; Habibullah, Muzafar Shah; Mohamed, Azali; Ahmad Sidique, Shaufique Fahmi (Faculty of Economics and Management, Universiti Putra Malaysia, 2018)
This paper explores the implications of economic globalisation on the environment based on the revised KOF globalisation index for 76 middle-income nations from 1994 to 2014. The System Generalised Method of Moments (GMM) is adopted for a 7-year span panel data to examine the implications of economic globalisation on environmental sustainability based on the Environmental Kuznets Curve (EKC) hypothesis. Unlike prior studies, the economic globalisation index is examined from both the de facto and de jure perspective to determine its impact on climate change. The over-arching results indicate no evidence of the validity of the EKC hypothesis amongst the middle-income nations, with primary energy consumption as the major driving force of carbon emissions. Urbanisation and population growth are negatively correlated with carbon emissions. Based on our findings, it is imperative for policymakers in middle-income nations to identify potential trade barriers and investments restrictions that could thwart the emergence of green technology adoption to combat climate change.